Modeling Enzymes Inhibition During Microparticles Formation - J. Kulys (Nonlinear Analysis, 2003)
A mathematical model of enzymes inhibition during microparticles formation has been developed. The model is based on radial substrate diffusion through diffusion layer that surrounds microparticle. The inhibition of enzymes was explained by enzyme adsorption on surface of the microparticles and substrate diffusion limitation through the diffusion layer. The diffusion module is dependent on dimensions of the microparticle. The microparticles with diameter 2 µm may ensure 50% of an apparent activity decrease if half of peroxidase has been adsorbed. Further adsorption of peroxidase and aggregation of the microparticles increases the apparent inhibition.